The Influence Financial Distress, Profitability , Company Size and Tax Incentives on Conservatism Accounting in Listed Transportation Sector Companies at BEI Period 2020-2022 " - Anggrainy, Dian; Alliyah, Siti (Jurnal Akuntansi, 2025)
Accounting conservatism ensures that companies respond carefully to inherent uncertainties and handle internal uncertainties and risks in the business environment appropriately. This study aims to examine the effect of financial distress, profitability, company size and tax incentives on accounting conservatism in transportation sector companies for the period 2020-2022. In this study, accounting conservatism as the dependent variable while financial distress, profitability, company size and tax incentives as independent variables. The population used is all transportation sector companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. The data collection technique applied is purposive sampling, which is in accordance with the research criteria. The research sample consisted of 24 which resulted in 72 observations. Data analysis was carried out by multiple linear regression after first being tested with classical assumptions to ensure the data met the best linear unbiased estimate (BLUE) requirements. The results showed that financial distress and profitability have a significant positive effect on accounting conservatism, company size has a significant negative effect on accounting conservatism and tax incentives have an insignificant negative effect on accounting conservatism."